Evaluation of the Human Health Risk of Wild Edible Mushrooms Consumption from Batak Mountain, Bulgaria - Miroslava IVANOVA; Lilko DOSPATLIEV; Denitsa GRIGOROVA; Penko PAPAZOV (Tehran University of Medical Sciences, 2020)
No Abstract